Incentives and inhibitors of abusing academic positions: analysing university students´ decisions about bribing academic staff - Graeff, Peter (European sociological review, 2014)
In a web-based survey, we presented university students (n = 2,287) with vignettes in which they had to decide whether to abuse the position of student assistant for personal gain. Referring to the existing literature, we tested whether the emergence of corruption increases when benefits from corruption and the probability of the occurrence of those benefits rise and whether corruption decreases when costs and the probability of their occurrence increase. These four factors were varied within a factorial survey design. Moreover, social norms against corrupt practices were measured. We tested whether such norms reduce the willingness to commit these practices. Our study is the first to simultaneously scrutinize these influences of corruption in universities. The results suggest that students deliberate on the pros and cons of corrupt behaviour. Higher risks or costs of corrupt activities appear to be significant deterrents. Higher benefits or success probabilities increase the likelihood of engaging in corrupt activities. However, these factors are less important than the social norms against corruption. As a consequence, our results imply that curbing corruption by monitoring and sanctioning might be less effective than stimulating social norms against corruption or strengthening the validity of fairness norms.